Enhancing Students' Reading Interest Through PQ4R Strategy Assisted by Comic Media at MI Muhammadiyah Panican - Dedy Irawan; Laksono Yogi Wibowo; Agung Nugroho; Sri Muryaningsih (Journal of Childhood Development, 2024)
Reading is a fundamental activity that affects every individual in learning various kinds of knowledge. Reading activities can become the foundation of an individual that supports the character formation process. Teaching reading is not an easy task because it requires the preparation of several things, such as environmental conditions, teaching techniques, learning strategies, and others. This research was motivated by the low interest in reading among sixth-grade students of MI Muhammadiyah Panican in Indonesian language learning. This study aims to provide solutions to the low reading interest of students through the implementation of the PQ4R strategy assisted by Comic media in the Indonesian language learning of the sixth grade at MI Muhammadiyah Panican. The research method used was Classroom Action Research (CAR), which was conducted in two cycles. The subjects of this study were the sixth-grade students of MI Muhammadiyah Panican, totaling 17 students. The results showed that the students' reading interest in the first cycle had reached a percentage of 64% with fewer criteria, while in the second cycle, it had obtained a percentage of 80% with good criteria. The research by applying the PQ4R strategy assisted by Comic media in the Indonesian language learning of the sixth grade at MI Muhammadiyah Panican has successfully increased the students' reading interest according to the expected success indicators